From advocacy to action: civil society and development agencies engaging the private sector actors to improve nutrition in Africa - Mittal, Navneet; Wallace, Fiona; Mukumbi, Kudzai (Frontiers in Sustainable Food Systems, 2025)
BackgroundAfrica has a triple burden of malnutrition. The private sector can affect the nutritional status of the population. To improve nutrition, civil society and development agencies are developing initiatives to engage these actors. The objectives of this study were to (a) identify and describe these initiatives and (b) understand their successes and challenges.MethodsAn exploratory research design, including an online search, the author’s knowledge, and generative artificial intelligence, was used to develop a list of potential nutrition initiatives. Publicly available data on these initiatives was included in an Excel template. Initiatives with a nutrition focus were shortlisted using an inclusion and exclusion criterion. In-depth review of data and semi-structured interviews were conducted with shortlisted nutrition initiatives for further insights.ResultsForty-eight initiatives were identified. Of these, twenty-four were multi-country with African presence, and twenty-four were Africa-only. Eight initiatives were shortlisted for in-depth review. Three more were added based on advice from an interviewee. Most initiatives were founded between 2011 and 2015. Private sector actors of varied sizes, operating in diverse food value chains, were engaged by the lead agencies. However, these actors were focused on food processing and manufacturing, with only some initiatives engaging the food retailers. The civil society and development agencies worked with the private sector through convening meetings, collaboration on projects, capacity building through training, and encouraging the private sector to make public commitments and monitoring them. Frequently reported initiative successes included an increased recognition by governments on the need to engage with the private sector on nutrition improvements. Frequently shared challenges were limited resources (financial and human) and an unclear business rationale to invest in nutrition. Key recommendations for the future were to ensure an appropriate structure with the right partners, an aligned vision, a robust governance process, and regular communication.ConclusionMulti-country initiatives led by civil society organisations or development agencies are engaging the private sector to improve nutrition in Africa. These initiatives operate using different approaches to influence private sector actions. This study fills an important knowledge gap by identifying and describing such initiatives and presenting their successes and challenges for future initiatives design and execution.